Do Human Papilloma Virus and Cytological Testing Results Before Colposcopy Alter the Pathological Grading of Colposcopy Acetic Acid Visual Examination?: A Retrospective Study - Gao S; Qian B; Wang T; Wang J (International Journal of Women's Health)
Songkun Gao,1 Boyang Qian,2 Tong Wang,1 Jiandong Wang1 1Gynecologic Oncology Department,Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, 100026, People’s Republic of China; 2Nantong University, Nantong, Jiangsu, 226019, People’s Republic of ChinaCorrespondence: Tong Wang; Jiandong Wang, Gynecologic Oncology Department,Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, 100026, People’s Republic of China, Email fcyywt@ccmu.edu.cn; wangjiandongxy@ccmu.edu.cnObjective: To understand whether human papillomavirus (HPV) and cytological testing (TCT [ie, “thinprep” cytological testing]) results can provide more information beyond visual information for vaginal colposcopy examinations to upgrade or downgrade the visual diagnosis of vaginal colposcopy.Patients and Methods: Data from 519 patients, who underwent vaginal colposcopy at the Beijing Obstetrics and Gynecology Hospital (Beijing, China) between January and June 2020, were included. Preoperative HPV and TCT results were statistically analyzed, and were divided into 3 groups according to postoperative cervical tissue pathological diagnosis: negative; low-grade squamous intraepithelial (LSIL); and high-grade squamous intraepithelial lesion (HSIL). Positive and negative predictive values for cervical inflammation, LSIL, and HSIL in patients diagnosed using vaginal colposcopy, based on cervical pathological grouping, and differences in HPV and TCT results among patients who underwent vaginal colposcopy, were analyzed.Results: The age of patients diagnosed with cervicitis, LSIL, and HSIL using colposcopy gradually decreased, and the proportion of HPV16/18 infection in the HSIL group was significantly higher than the other 2 groups. There were significant differences in TCT results among the groups. According to pathological results from cervical tissue specimens, among all groups diagnosed using colposcopy, the age of the HSIL group was significantly younger than that of the other groups, and the proportion of patients with a TCT greater than LSIL was significantly higher than that of the other groups.Conclusion: HPV did not provide additional information for vaginal colposcopy. Young(er) patients and those with a TCT greater than LSIL may consider upgrading the vaginal colposcopy diagnosis based on imaging information.Keywords: vaginal colposcopy acetic acid visual diagnosis, cervical precancer, HPV, TCT